Development and Validation of RP-HPLC Method for the Estimation of Gemifloxacin Mesylate in Bulk and Pharmaceutical Dosage Forms - Yunoos Mohammad; B. Pragati Kumar; Azmath Hussain; Harish (E-Journal of Chemistry)
A simple, rapid, accurate, precise and reproducible reverse phase high performance liquid chromatographic method has been developed for the estimation of gemifloxacin mesylate in bulk and pharmaceutical formulations. The quantification was carried out using cyberlab capcell pak, ODS C18 (250 × 4.6 mm i.d., 5 μm particle size) column in an isocratic mode, with mobile phase comprising Buffer (KH2PO4 with pH 6.8): acetonitrile in the ratio of 80:20 (%v/v).The flow rate was at 1.2 mL/min and the detection was carried out at 265 nm. The retention time of the drug was found to be 7.47 min and the method produced linear response in the concentration range of 25-150 μg/mL (R∼0.99986). The recovery studies were also carried out and % RSD from reproducibility was found to be 0.82. The proposed method was statistically evaluated and can be applied for routine quality control analysis of gemifloxacin mesylate in tablets.